A production and operations management study on Fortune Tobacco Corporation - Biton, Dennis Paul L. (College of Engineering, 2000)
A Production and Operations Management study was conducted on Plant A of Fortune Tobacco Corporation (FTC) which manufactures Class C cigarettes sold locally in the provinces. The study included documentation, evaluation and analyses of the facility's present production system, forecasting, strategic planning, aggregate planning, and identification of possible improvement areas along with their corresponding recommendations. The process documented was that of the Class C cigarettes classified according to cigarette length -- size 100's and Kings. All documentation of company systems was analyzed for the purpose of evaluation. forecasting the demand for the class C Cigarettes was facilitated through the Decomposition of a Time Series through Simple Proportion Technique, evaluated through its tracking signal. The monthly forecasts for the year 2000 was used as the basis for planning future capacity and workforce level requirements. Analyses of the current system resulted in the identification of the following problem areas: (1) lack of worker motivation; (2) in job enrichment program; and (3) lack of coordination across production divisions. To address the problem areas, the implementation of the following recommendations were presented: (1) Worker Motivation Program -- focusing on the importance and recognition of the contribution of the company's workforce resource; (2) Job enrichment Program -- characterized by added responsibility for the workers; and (3) Coordination of the Operations of the Three Divisions, -- emphasizing on operations synchronization highlighted by a preventive maintenance program. In addition, the monthly forecasts for the year 2000 were recommended to be the basis of the company's production. Using the forecasted values as the basis, strategic capacity recommendations include: (1) The carrying of inventory in the Tobacco Leaf Processing Division from months of negative capacity gaps towards months of positive capacity gaps; (2) The sharing of making machines and the purchase of more during months when sharing could not take place; and (3) A redistribution of excess packing machines in one operation to fill in the needed capacity requirements of the other. Lastly, it was recommended that a constant workforce level of 528 workers be implemented. This scheme yielded the lowest annual cost across all alternatives considered.